EFEKTIVITAS PROGRAM GERMAS DINKES KOTA MAKASSAR DALAM PENINGKATAN STATUS KESEHATAN JAMAAH HAJI TAHUN 2018 - Ilham, Muhammad Nashrullah; Patimah, Sitti; Alwi, Muhammad Khidri (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Muhammad Nashrullah Ilham. The Effectiveness of the Germas Program of the Makassar City Health Office in Improving the Health Status of Hajj Pilgrims in 2018 (Guided by Sitti Patimah and H. Muh. Khidri Alwi). This study wants to assess the effectiveness of the program of the Healthy Living Society Movement (GERMAS) of the Makassar City Health Office in Improving the Health Status of Hajj Pilgrims in 2018. This research uses a mixed approach (Mix Design). The Mix Design research approach is dominant-less dominant, which is dominant in this research, namely the qualitative approach, while the less dominant one is the quantitative approach. The key informants in this study were 42 pilgrims from the City of Makassar. Ordinary informants were health workers involved in the Society Life Healthy Movement program in pilgrims as many as 5 people. The results of the study show that at the input, process and output stages have been going well. The results of the statistical analysis showed a change in the health status of the pilgrims after the implementation of the Healthy Living Society Movement (GERMAS) namely significant changes in blood pressure (p = 0.001), changes in obesity status (p = 0.310), blood sugar levels (p = 0,000) and also a significant change in gout (p = 0.145). The conclusion of the study is that starting from the input, process and output are in accordance with the program expectations. It is recommended that there be a continuous socialization of the GERMAS program to the general public and carried out also by all government and private agencies. Keywords : Effectiveness, healthy living society movement, hajj pilgrims